THE RELATIONSHIP BETWEEN SCHOOL ENVIRONMENT AND LEARNING INTEREST WITH THE FOURTH GRADE STUDENTS LEARNING ACHIEVEMENT OF SOCIAL SCIENCE LESSON - Rokhayati, Tri (Joyful Learning Journal, 2017)
Abstrak Penelitian ini bertujuan untuk mengetahui hubungan lingkungan sekolah dan minat belajar dengan hasil belajar IPS siswa kelas IV SDN Gugus Cendrawasih Kecamatan Mlonggo Kabupaten Jepara. Penelitian ini merupakan penelitian korelasional dengan jenis penelitian kuantitatif dengan sampel sebanyak 100 siswa yang diambil menggunakan teknik Proportional Cluster Random Sampling. Alat pengumpul data berupa kuesioner, tes soal dan dokumentasi. Analisis data terdiri dari analisis deskriptif, analisis data awal/uji prasyarat analisis, analisis data akhir menggunakan uji hipotesis dan analisis regresi. Hasil penelitian menunjukkan bahwa : (1) terdapat korelasi yang positif dan signifikan lingkungan sekolah dengan hasil belajar IPS dengan koefisien korelasi sebesar 0,640; (2) terdapat korelasi yang positif dan signifikan minat belajar terhadap hasil belajar IPS dengan koefisien korelasi sebesar 0,665; (3) terdapat korelasi yang positif dan signifikan lingkungan sekolah dan minat belajar dengan hasil belajar IPS dengan koefisien korelasi sebesar 0,696. Berdasarkan penelitian tersebut, dapat disimpulkan bahwa bahwa terdapat hubungan lingkungan sekolah dan minat belajar dengan hasil belajar IPS siswa kelas IV SDN Gugus Cendrawasih Kecamatan Mlonggo Kabupaten Jepara. Saran berdasarkan hasil penelitian ini adalah guru hendaknya menyesuaikan kondisi lingkungan sekolah dan meningkatkan minat belajar siswa. This study was aimed at knowing the relationship between school environment and learning interest with the fourth grade students' learning achievement of social science lesson (IPS) in State Elementary Schools Cluster Cendrawasih, Mlonggo subdistrict, Jepara District. Moreover, this study belonged to correlational study with quantitative approach. Further, the sample of this study many as 100 students taken by Proportional Cluster Random Sampling technique. The data collection techniques were questionnaire, test and documentation. The data analysis covered descriptive analysis, initial data analysis/ prerequisite analysis, and final data analysis using hypothesis test and regression analysis. The results showed: (1) there was a positive and significant correlation between school environment and the learning achievement of IPS lessonwith correlation coefficient of 0.640; (2) there was a positive and significant correlation between learning interest andthe learning achievement of IPS lesson with correlation coefficient of 0.665; (3) there was a positive and significant correlation between school environment and learning interest with IPS lesson's learning achievement with correlation coefficient of 0.696. Based on the findings, it can be concluded that there is a relationship between school environment and learning interest with the IPS lesson's learning achievement ofthe fourth grade students ofState Elementary Schools Cluster Cendrawasih. Mlonggo Subdistrict, Jepara District. Furthermore, it is suggestedthat teachers should be supposed to adapt with the school environment andimprove students' learning interest.